Optimization of Additive Combination Based on l‐Cysteine for Inhibition of Nonenzymatic Browning in Cooked Rice during Storage. Issue 5 (28th April 2014) - Zhao, Peicheng; Deng, Shasha; Ding, Yuting; Lyu, Fei
Abstract The aim of this study was to optimize the concentrations of l‐cysteine (l‐cys), composite phosphate (CP) and sucrose ester of fatty acid (SE‐15) in the immersion solution to inhibit the yellowness and to maintain sensory score of cooked rice during storage. The well‐fitted regression equations both for the yellowness and for the sensory score of cooked rice were obtained, with the R2 values of 0.946 and 0.881, respectively. The predicted lowest yellowness and highest sensory score were 5.619 and 82.801, and the optimized concentrations of l‐cys, CP and SE‐15 were 0.03, 0.16 and 0.15%, respectively. The verification results showed that the lowest yellowness and highest sensory score were 5.633 and 82, which was in accordance with the predicted value. Practical Applications Cooked rice is one of the most important ready‐to‐eat meals in human daily life. But during storage, it is easy for them to undergo non‐enzymatic browning reaction, which has an influence on the color and sensory quality of cooked rice and reduce the commercial value for cooked rice. The main utility of this research is the application of food additive combinations based on l‐cysteine in cooked rice, which can be considered a novel technique to maintain the quality of cooked rice during storage. The color and sensory analyses on stored cooked rice can confirm that the combined food additives of l‐cysteine, composite phosphate and sucrose ester of fatty acid could inhibit the yellowness and maintain sensory score of cooked rice during storage. The use of this technique could maintain the quality of cooked rice and increase its commercial value.